Local Economic Development Based on Regional Potential as a Means of Increasing Community Participation in Tanjung Laut Indah - Rabiah , Siti; Ratna Kusuma , Aji; Rande , Santi; Oyekan, Margaret (JED (Jurnal Etika Demokrasi), 2025)
Limited and uneven community participation remains a critical barrier to local economic development, particularly in resource-rich peripheral regions where externally driven interventions frequently fail to generate inclusive and sustainable outcomes. This study therefore aims to analyze the patterns, determinants, and implications of community participation in local economic development in Tanjung Laut Indah Village, Bontang City, East Kalimantan, with a particular focus on how regional potential can be strategically leveraged to strengthen participatory processes and outcomes. A qualitative research design was employed, combining in-depth interviews, participatory observation, and document analysis; the data were interpreted using the Sustainable Livelihood Framework to examine the interactions among natural, human, social, physical, and financial capital. The findings indicate heterogeneous participation typologies: approximately 45% of residents engage in active participation, 30% participate passively, 15% are not involved, and 10% display counterproductive or resistant behaviors. Active participation is concentrated among fishermen, housewives operating micro-enterprises, and youth engaged in technology-based initiatives, demonstrating the potential of locally driven actions to create economic value, strengthen social cohesion, and support sustainable livelihood strategies. In contrast, passive, non-involvement, and resistance are shaped by top-down program designs, limited skills, resource constraints, institutional barriers, and conflicting interests that vary across demographic groups and over time. The study concludes that effective local economic development requires multidimensional, context-sensitive strategies that integrate capacity building, inclusive decision-making, and equitable resource distribution. The novelty of this research lies in its empirical classification of participation typologies explicitly linked to livelihood assets, providing a more granular understanding of participation dynamics. These results contribute conceptually and practically by informing policymakers and development practitioners in designing resilient, equitable, and participatory local economic initiatives that promote sustainable growth and community empowerment.